Athlete perceptions of virtual reality and barriers to its use in sport: A qualitative examination - Jarad A. Lewellen; Eric Baker; Peter R. Giacobbi (PLoS ONE, 2025)
Though research has demonstrated the practical utility of virtual reality (VR) in settings such as the military, medicine, and counseling, VR in sport has become a research focus only in the last several years. As such, it is important to understand how this evolving technology is perceived and accepted by athletes. The purpose of this qualitative study was to examine VR use among athletes with experience using VR technology, uncover potential barriers to VR use in sport, and explore possible solutions to these barriers. Fourteen athletes with previous experience using VR headsets participated in semi-structured interviews exploring their experiences and perceptions of VR. The interviews were transcribed, cleaned, and coded in line with Braun and Clarke’s qualitative framework. Using inductive and deductive analyses, we observed nine primary themes: where, when, why, what, frequency and duration, experience, acceptance, primary barriers, and overcoming barriers. Participants suggested a hesitancy among athletes and coaches to accept and adopt VR as a training tool. The primary barriers to adoption were cost, cybersickness, coach attitudes, awareness, understanding, and visibility. Applied implications focus on addressing and overcoming barriers by providing VR education and training to potential users and increasing accessibility to VR. Future research should expand to other populations (e.g., youth and professional athletes) and different versions of VR and extended reality technology (e.g., mixed reality), as well as examine effective ways to implement VR in applied settings. This study provides insight on athletes’ perceptions of VR and contributes to the growing foundation of VR literature in sport.